2018
DOI: 10.1590/2318-0331.231820180043
|View full text |Cite
|
Sign up to set email alerts
|

Forest restoration and hydrological parameters effects on soil water conditions: a structural equation modelling approach

Abstract: Although the effects of land use changes on hydrological functioning are widely addressed, issues such as which components of the hydrological system are affected, how and on what time scales are still poorly understood. In this context, we evaluated whether forest restoration improves soil water conditions in a Cerrado area, and whether the combined effects of forest structure and hydrological variables influence soil attributes. For this, we monitored three areas in different stages of natural succession ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Generally, soil infiltrability is closely related to the type of vegetation cover [14]. Infiltration rates are usually higher when the vegetation size and cover are larger, especially when trees provide the cover [3,22,29,68]. Gilmour et al [30] found improved infiltration rates in reforested areas that were 5 and 12 years old (51 and 524 mm•h −1 , respectively) and in native forests (370 mm•h −1 ), compared with deforested lands or those converted to heavily grazed grasslands (39 mm•h −1 ).…”
Section: Infiltration and Runoffmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, soil infiltrability is closely related to the type of vegetation cover [14]. Infiltration rates are usually higher when the vegetation size and cover are larger, especially when trees provide the cover [3,22,29,68]. Gilmour et al [30] found improved infiltration rates in reforested areas that were 5 and 12 years old (51 and 524 mm•h −1 , respectively) and in native forests (370 mm•h −1 ), compared with deforested lands or those converted to heavily grazed grasslands (39 mm•h −1 ).…”
Section: Infiltration and Runoffmentioning
confidence: 99%
“…Some authors reported that infiltration rates increased after forest restoration, compared to the rates of deforested areas [3,6,7,33,37,39,40,42]. Bessie et al [68] reported improved soil infiltration rates at sites where natural vegetation was recovering. In our study, the soil infiltration rate of oak forest is lower than that of pinewood (660.67 mm•h −1 compared to 857.67 mm•h −1 ).…”
Section: Infiltration and Runoffmentioning
confidence: 99%
“…Canopy interception occurs when the rainwater retained on the rainforest leaves and trunks is subsequently lost by evaporation and returned to the atmosphere. In this sense, environmental services are those provided by nature itself which are essential for maintaining the ecological balance (WUNDER et al, 2008) since, depending on the category of the forest, they can significantly interfere with the water balance of hydrographic basins (BESSI et al, 2018). For example, they can reduce river flow fluctuations throughout the year, and delay or decrease flood peaks (TUCCI, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Canopy interception tends to reduce the fluctuations in the flow of surface water bodies and groundwater (BESSI et al, 2018) throughout the year, delaying or reducing maximum flows and flood peaks, and also preventing the excessive impact of part of the rainwater on the soil. Furthermore, it interferes with the Amazonian climate pattern, since interception by dense canopies might favour a greater return of water to the atmosphere, especially during dry periods (DOUGHTY et al, 2015;OLIVEIRA et al, 2011;CUARTAS et al, 2007;SALESKA et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Stemflow can be defined as the intercepted rainwater collected by the stem that passively descends to the roots through gravity (BID-DICK; HUTTON; BURNS, 2018;BESSI et al, 2018a;BESSI et al, 2018b) and has been recognized as an essential process of water supply to spatially located areas of forest soil (TANAKA et al, 2017). According to Levia and Germer (2015), many researchers recognize stemflow as an important phenomenon that can have considerable effects on ecosystem hydrology, biogeochemistry, and ecology.…”
Section: Introductionmentioning
confidence: 99%